ENVISAT ASAR measurements of marine parameters - Lehner, Susanne; Schulz-Stellenfleth, Johannes; Hoja, Danielle; Horstmann, Jochen (Wissenschaft & Technik Verlag Berlin, 2001)
The European satellite ENVISAT to be launched in January 2002, carries several new radar instruments, which are well suited for oceanographic measurements. This paper gives an overview of different oceanographic applications of active microwave radar data. Studies on wind and sea ice parameter retrieval are presented in more detail. Synthetic aperture radar data acquired by the European remote sensing satellite ERS-2 were reprocessed to ENVISAT like data products using the BSAR processor developed at the German Aerospace Center (DLR). Every day about 1000 SAR images of 5 km x 10 km size every 200 km along the satellite track are available thus yielding global and continuous coverage of the oceans. The dataset is used to analyze SAR image features on a statistical basis. In particular wind streaks are used to gain information on wind direction. Furthermore imagette data are used to derive sea ice variables by applying image analysis techniques.